Knowledge-based parametric design and collaboration - Wang, Zhonghui. (2008)
This study attempts to solve multiple-view problems by incorporating the technique of constraint-based parametrization for single 2D model with the proposed concepts of entity influence lines. Based on the descriptive geometry, entity projection rules and reasoning rules are incorporated to deal with the multi-view constraint schema. The multiview model to be addressed is expressed in three orthographic views, and illustrative examples are presented to show the practicability of the method.